Adrenal hemorrhage in neonates: Incidence, perinatal characteristics and follow-up outcomes - Tek-Jū Tân; Yi-Li Hung; Chung-Min Shen; Wu-Shiun Hsieh (Pediatrics and Neonatology)
Background and objectives: Neonatal adrenal hemorrhage (NAH) is relatively uncommon in neonates and it is often noted accidently by abdominal ultrasonogram. Few studies discussed risk factors for and impacts of NAH. This study aimed to assess incidence, perinatal characteristics and follow-up outcomes in neonates with adrenal hemorrhage. Methods: This was a retrospective cohort study in a single institute from April 2008 to August 2018. All neonates who received abdominal ultrasonogram within seven days-of-life were recruited and divided in to 2 groups according to the presence of NAH. The perinatal characteristics and anthropometric measurements, the follow-up course and the clinical impact of NAH were reviewed in detail. Results: 7217 neonates had received abdominal ultrasonogram within seven days-of-life and 29 of them (0.4%) were diagnosed with NAH. Mean gestation age was 38 ± 1.2 weeks and mean birth weight was 3406 ± 403 g. Most infants (96.6%) had unilateral hemorrhage over the right adrenal gland. Compared with the control group, infants with NAH were significantly heavier (3406 vs. 3094 gm, p < 0.001), longer in body length (50.1 vs. 48.8 cm, p < 0.001) and wider in chest girth (33.2 vs. 32.4 cm, p = 0.006). They also tended to be delivered via vaginal delivery with vacuum-extraction rather than cesarean section. The prevalence of nuchal cord, neonatal jaundice and subgaleal hemorrhage was higher in the NAH group. The hemorrhage area of adrenal gland had a positive correlation with the peak bilirubin level (r = 0.422, p < 0.001) and the days to resolution (r = 0.198, p = 0.033). All infants had resolution of AH before 7 months of age. Conclusions: NAH occurred more frequently in heavier neonates that were delivered via vaginal delivery with vacuum extraction. The hemorrhage involved mostly over the right adrenal gland. Neonatal jaundice was the major comorbidity. All infants had spontaneous resolution of AH before 7 months of age.